Community systems models and development scenarios for integrated planning: Lessons learned from a participatory approach. Issue 3 (26th May 2020) - Newell, Robert; Picketts, Ian; Dale, Ann
ABSTRACT: Systems models can support community planning, and by engaging local government and community stakeholders, these models can be designed to capture a comprehensive but manageable range of key interests, concerns, and values. This study explores a participatory approach for designing a community systems modeling exercise. The research involved convening focus groups of local government and diverse community stakeholders in Squamish, Canada, in order to discuss local issues and possible futures for the community. Focus group feedback was used to inform the development of a model of relationships between development paths (reflecting different densities) and multiple community outcomes, such as access to amenities and education, walkability, parks/trails, food and farm systems, public transit, housing affordability, and local employment. A participatory approach to modeling yielded many benefits, including alignment with normative participatory planning concepts, effective model scoping, accessing additional information sources, and enhancing local social capital and investment in the project.